The Effect of a Textile-Reinforced Mortar on the Flexural Response of Energy-Improved Infill Walls - André Furtado (2022)
The existing infilled reinforced concrete (RC) buildings' poor energy performance is responsible for a significant part of the energy consumption in the European Union (EU). In addition, recent earthquakes showed the seismic vulnerability of the existing RC buildings that were not designed according to modern codes, where several casualties, collapses, and economic losses were reported. Around 40% of the EU buildings are located in seismic regions and designed with substandard safety requirements, of which 65% need both energy and seismic retrofit. New strategies are necessary to simultaneously improve the energy efficiency and seismic vulnerability of new constructions. Apart from the modern seismic and energy codes, new materials are being developed by the construction industry that can play a significant role in the next few decades. Based on this motivation, this paper aims to study the efficiency of using textile-reinforced mortar (TRM)-based solutions to improve the seismic behavior of masonry infill walls made of lightweight and energy-improved masonry blocks. This holistic strategy is designed for new constructions. For this, eight strengthened energy-improved infill walls were subjected to flexural strength tests to validate the TRM efficiency using a low-strength and a high-strength textile mesh and study the effect of using connectors. All the tests consisted of applying a monotonic out-of-plane tests were performed through a one-point load approach. The results will be presented in terms of out-of-plane force-displacement responses, flexural stress, and damage evolution. Lastly, a state-of-the-art discussion is carried out to analyze possible relationships between the textile mesh tensile strength and the flexural strength of the walls.